2015
DOI: 10.4049/jimmunol.1500602
|View full text |Cite
|
Sign up to set email alerts
|

BTB-ZF Protein Znf131 Regulates Cell Growth of Developing and Mature T Cells

Abstract: Many members of the BTB-ZF family have been shown to play important roles in lymphocyte development and function. The role of zinc finger Znf131 (also known as Zbtb35) in T cell lineage was elucidated through the production of mice with floxed allele to disrupt at different stages of development. In this article, we present that Znf131 is critical for T cell development during double-negative to double-positive stage, with which significant cell expansion triggered by the pre-TCR signal is coupled. In mature T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…Miz1 is necessary for early T cell development by functioning downstream of IL7 receptor signaling [67, 117]. Finally, Zbtb35 KO mice show severe impairment in the transition from CD4/8 double-negative to double-positive stages [118]. …”
Section: Zbtb Function In Hematopoietic Developmentmentioning
confidence: 99%
“…Miz1 is necessary for early T cell development by functioning downstream of IL7 receptor signaling [67, 117]. Finally, Zbtb35 KO mice show severe impairment in the transition from CD4/8 double-negative to double-positive stages [118]. …”
Section: Zbtb Function In Hematopoietic Developmentmentioning
confidence: 99%
“…Ablation of ZNF131 in the DN2/DN3 thymocytes (Lck-Cre) does not affect γ δ + T cell development, but significantly reduces the numbers of DN3, DN4 & DP cells, especially the latter two populations ( 72 ). Although the rearrangement of TCR-β locus is intact in ZNF131-deficient DN3 cells, ZNF131 represses the expression of CDKN1A (cyclin dependent kinase inhibitor 1A, also known as P21 Cip1 ) by directly binding to its promoter region, and therefore promotes the (pre-)TCR-induced proliferation of thymic DN3/4 & peripheral mature T cells ( Figures 1A , 2A, B ).…”
Section: Zbtb Proteins Regulating Both the Development And Function Of T Cellsmentioning
confidence: 99%
“…In addition, depletion of ZNF131 at the DP stage (CD4-Cre) has no impact on the survival & differentiation of DP toward CD4 or CD8 SP cells in the thymus. Thus, ZNF131 is mainly involved in the DN-to-DP transition of thymocytes and the homeostasis/proliferation of mature T cells via suppressing CDKN1A ( 72 ). Recently, the same group showed that ZNF131 promotes the early B cell development via similar mechanisms ( 73 ).…”
Section: Zbtb Proteins Regulating Both the Development And Function Of T Cellsmentioning
confidence: 99%
“…38 It has also been shown that p21 expression is suppressed in T cells by the zinc finger protein Znf131, thus controlling proliferation of T cells. 39 To further ascertain that p53 is induced by the cMycp14ARF pathway, we inhibited cMyc using 10058-F4, 25 a small-molecule inhibitor that interferes with cMyc/Max heterodimerization, blocking cMyc-mediated transactivation. 40 10058-F4 suppressed cMyc protein expression in activated T cells and also inhibited T cell proliferation.…”
Section: Discussionmentioning
confidence: 99%